Performance of Fiber Optics with Response Low Fat Milk and Full Cream Milk Towards Hydrogen Peroxide - Mohad Yusoff Shah, Nurul Ain; Nurul Nadia Adnan,; Nurul Athirah Mohd Taib, (Enhanced Knowledge in Sciences and Technology, 2024)
A Fiber Optic Displacement Sensor (FODS) utilizing reflective intensity modulation to assess hydrogen peroxide concentrations in low-fat and full-cream milk. The chemiluminescence technique approach which is currently used to measure hydrogen peroxide concentration in milk, has limitations such as suffering from the interference of some cations, which may affect the accuracy of the detection process. Thus, an intensity-modulated based sensor composed of optical fiber was developed to determine the concentration of hydrogen peroxide in low-fat milk and full-cream milk. The developed transmissive optical sensor, focusing on the 0% - 10% range of hydrogen peroxide concentration. The sensor exhibits remarkable performance, yielding a sensitivity of 0.008 V/% for low-fat milk with a linearity exceeding 97%, and 0.007 V/% sensitivity for full cream milk with a linearity surpassing 97%. The approach outlined offers a practical solution for assessing hydrogen peroxide levels, a potential adulterant and ensuring consumers' milk products' safety.